Comparing the Performance of the SF-6D and the EQ-5D in Different Patient Groups - Ferreira, Lara N. (2014)
Introduction: This research aims to explore the performance of the SF-6D and the EQ-5D in patients suffering from asthma, chronic obstructive pulmonary disease, cataracts, and rheumatoid arthritis. In particular, the aim of this research is twofold: 1) to study the level of agreement between the indexes and the descriptive systems of the dimensions of the SF-6D and the EQ-5D, and 2) to analyze the discriminative ability of the instruments.Material and Methods: A sample of 643 patients completed both the SF-36v2 and the EQ-5D. The discriminative ability of the instruments was analyzed. Furthermore, the level of agreement between the indexes and the descriptive systems of the dimensions of the SF-6D and the EQ-5D were studied. The level of agreement between instruments was investigated using correlation coefficients and the Bland-Altman plots, while the influence of medical condition and other socio-demographic variables was analyzed using nonparametric tests. Paired-samples tests were used to identify differences between the scores.Results and Discussion: The results show a strong correlation and agreement between both indexes. Overall, questionnaire indexes differ by medical condition and socio-demographic groups and both instruments are able to discriminate between socio-demographic groups.Conclusion: This study confirmed the hypothesis that the SF-6D generates higher utility values in less healthy individuals. The SF-6D and the EQ-5D seem to perform differently in each of the diseases studied since the descriptive statistics differ between instruments and the level of correlation is not uniform. Results show that the instruments generate different utility values, but there is a strong agreement between both indexes. Thus, the two instruments are not interchangeable and their results cannot be directly comparable.